Urgent surgery due to hemorrhagic rupture in giant gastrointestinal stromal tumor - Navarro-Martínez, Sergio; Pérez Rubio, Álvaro; Sebastián Tomás, Juan Carlos; Ortiz Tarín, Inmaculada; de Pozo, Carlos Domingo (Cirugía del Uruguay, 2020)
Mesenchymal tumors account for 1% of primary malignant gastrointestinal tumors. The most frequent location is the stomach and their average size is a few centimeters at diagnosis. We present the case of a 79-year-old male who was admitted for sudden dyspnea. He was diagnosed with pulmonary thromboembolism (PTE) and treated with anticoagulants. The tomography showed a mass compatible with a gastrointestinal stromal tumor of 18 centimeters dependent on the gastric anterior face. During admission, the patient experiences hypotension and sudden anemization. The tomography was repeated, showing an increase in size secondary to intratumoral hemorrhage, indicating urgent surgery.